Why go to the Emergency Room? A Patient Decision Making Process - Hanson, William; Moore, Jeffrey; Whitesides, Chandler; Foxx, Madison; Hickman, Joshua; Ramirez, Manny; Jordan, Evan (International Journal of Management Excellence (ISSN: 2292-1648), 2014)
The purpose of this case study is to understand what influences patient decisions to go to the emergency room. This case study is discovery oriented, listening to patient perspectives and providing a model for health care providers and policy makers to discuss. The research setting is a regional hospital in the southeast, with a sample of 20 patients meeting pre-set criteria. Using qualitative methods, we code our data using well-tested methods of Strauss and Corbin. Our findings reveal four primary factors that play a significant role in the patients’ decision. Factors include severity of condition or pain, convenience, reputation, and external referrals. Upon conditions creating concern or pain, patients either self-refer to the ER, or report to their primary care physician or a public or urgent care clinic. If they go to their primary care physician or an urgent care clinic, oftentimes the need for special tests or equipment cause medical professionals to direct the patient to the emergency room for those services. From these factors and their corresponding features, we produce a patient decision model for reporting to the emergency room. This model provides a way for hospitals to help identify strategies to help reduce emergency service demand.